Avaliação dos efeitos imunomoduladores das moléculas BD-8, BD-15 e digoxina em modelos de infecção com Mycobacterium smegmatis - Nogueira, Noêmia Nielly Amaral (2024)
Cardiotonic steroids are organic compounds that possess the ability to inhibit Na⁺/K⁺-ATPase. The literature has documented that ouabain and digoxin are endogenous molecules capable of interfering with various aspects of the immune response. Recently, new cardiotonic steroids were synthesized from digoxin: BD-8 (8-benzylidene digoxin) and BD-15 (15-benzylidene digoxin). However, little is known about the effects of these compounds on inflammatory and infectious processes. In this context, the aim of this study is to evaluate the effects of BD-8, BD-15, and digoxin molecules in Mycobacterium smegmatis infection models using the RAW 264.7 murine macrophage cell line. Initially, in vitro susceptibility assays were performed against Mycobacterium smegmatis. For the study of cell viability, the MTT colorimetric method was used with different concentrations (10 μM, 5 μM, 1 μM, 0.1 μM, and 0.01 μM) at 24, 48, and 72 hours. For the evaluation of therapeutic effects, Colony Forming Units (CFU) counts were performed in plate assays where RAW cells were infected with Mycobacterium smegmatis and treated with the steroids. Cytokine levels were measured using the enzyme-linked immunosorbent assay (ELISA) method. When evaluating the Minimum Inhibitory Concentration (MIC), it was observed that the molecules did not inhibit bacterial growth at concentrations lower than and equal to 200 μM. In the MTT viability results, BD-8 did not exhibit cytotoxic activity at 24 hours, but it showed cytotoxicity at 10 μM and 5 μM at 48 hours, and at 10 μM, 5 μM, and 1 μM at 72 hours. BD-15 did not exhibit cytotoxic activity at any concentrations or times tested and was selected as the synthetic steroid for further experiments. Digoxin did not exhibit cytotoxic activity at 24 hours but showed cytotoxicity at 10 μM and 5 μM at 48 hours, and at 10 μM and 1 μM at 72 hours. Regarding CFU counts, both BD-15 and digoxin reduced the number of CFUs per well at 10 μM after 24 hours compared to the control. The results obtained through the ELISA technique indicated that treatment with digoxin did not result in a statistically significant change in IL-10 production, showing only a marginal increase of 2% compared to the infected control. In contrast, treatment with BD-15 demonstrated a 19% increase in IL-10 production. Regarding IL-1β levels, a 58% reduction was observed with both digoxin and BD-15 treatments compared to the infected control. In terms of TNF-α production, digoxin treatment led to a 41% increase, while BD-15 treatment resulted in a 42% increase, both compared to the infected control. Static analyses were performed on the prism using mean ± standard error of the mean and one-way ANOVA followed by Tukey's test (p<0.05). Therefore, this study significantly enhances the understanding of the role of cardiotonic steroids in Mycobacterium smegmatis infection, offering new opportunities for the development of more effective and less toxic therapies for the treatment of mycobacterial infections.